Comparison of two configurations of upflow anaerobic filters : specific methanogenic activity profiles - Alves, M. M. (1996)
The aim of this work was to determine the distribution of microbial activity along the height of two configurations of anaerobic filters treating a synthetic dairy waste. A traditional configuration was compared with a staged system which had biogas removal from each of the three stages. The effect of increasing the substrate concentration from 3 to 12 g COD/l at constant hydraulic residence time (HRT) of 2 days was evaluated with respect to overall reactor performance, gas production and effluent volatile fatty acids profiles. The potential maximum specific methanogenic activity against acetate, H2/CO2 and an indirect substrate (propionate) was determined for sludge sampled from three different points in each reactor, under two operating conditions (influent COD of 3 and 9 g COD/l). The increase in influent concentration was shown to promote a stratification of the specific acetoclastic activity more pronounced in the staged reactor. Both the hydrogenophilic and acetoclastic activities were highest at the top of the filters, whereas the methanogenic activity against propionate was maximum in the middle section and was very similar for both reactor configurations. The results confirmed the reliability of the pressure transducer technique to study methanogenic activity of different trophic groups in consortia.